Falling Down a Deep Hole:: The Experience of an Identity Crisis as a Gestalt Therapist - Evans, Ken (European Journal for Qualitative Research in Psychotherapy, 2012)
Between February 25 and 26, 2012, around thirty Gestalt Therapists from five European nations (Sweden, Denmark, Fin- land, The Netherlands and the UK) gathered together to engage in an experientially based learning weekend on research in gestalt therapy. The event was organised by the Swedish Association for Gestalt Therapy - SAG Board and its energetic chair Jojo Tuulikki Oinonen. The weekend was facilitated by Ken Evans, former President of the European Association or Gestalt Therapy and co-author with Linda Finlay of Relational Centred Research in Psychotherapy: exploring meanings and purpose. (Finlay and Evans, 2009).